PELATIHAN DAN PRAKTIK PEMBUATAN MOKANUSA COOKIES CHEWY BERBASIS MOCAF DESA MERAK BATIN, KECAMATAN NATAR, KABUPATEN LAMPUNG SELATAN - sutarto sutarto; Ratna Dewi Puspita Sari; Irma Lusi Nugraheni; Bayu Anggileo Pramesona; Ramadhana Komala; Andi Eka Yunianto; Rebecca A F Saragih; Niam Musadad; Farid Kahar; Wijaya Kesuma; Ihsan Fajar Indriansyah Valian; Najwa Zaskia Suryadi; Kevina; Arina Dima Fasya; M Anugrah Arbi; Faras Raditia Maulana; Tamara Adela; Murni Kurniawati; Alvika Zahra (BUGUH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2026)
This community service program aimed to improve community knowledge and skills in utilizing mocaf flour as an alternative to wheat flour through training on producing MokaNusa Chewy Cookies in Merak Batin Village, South Lampung. The method applied a participatory approach involving education, hands-on practice, and continuous assistance. A total of 27 participants were involved, mostly aged over 40 years. The evaluation results showed an increase in average knowledge scores from 68.15 to 84.81, with an improvement of 16.66 points, and 70.4% of participants experienced increased knowledge. Participants were also able to independently apply the processing skills. This program proved effective in enhancing community capacity, promoting local food diversification, and creating opportunities for home-based businesses to support food security and economic empowerment.